PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR IPA MATERI EKOSISTEM RANTAI MAKANAN DI KELAS V SEKOLAH DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the low engagement and suboptimal learning outcomes in Natural Sciences (IPA) among fifth-grade students at SD Negeri 73 Maluku Tengah, particularly on the ecosystem food chain material, which stemmed from monotonous, teacher-centered instructional methods. The objective was to determine the effect of the Project Based Learning (PjBL) model on students’ learning outcomes. Employing a quantitative pre-experimental design with a one-group pretest-posttest approach, the research involved 25 fifth-grade students as the sample. Data were collected through pretest and posttest instruments, observations, and documentation. The analysis utilized descriptive statistics, normality and homogeneity tests, and a paired sample t-test to examine the hypothesis. The results indicated a significant improvement in learning outcomes: the pretest mean score was 61.44 with only six students meeting the completion criteria, whereas the posttest mean rose to 83.72 with 24 students achieving the criteria. The paired sample t-test yielded a significance value of 0.000 (< 0.05), confirming a statistically significant effect. Consequently, the application of the PjBL model effectively enhances fifth-grade students’ understanding and academic achievement in IPA, specifically on food chain concepts, by fostering active, collaborative, and project-based learning experiences.